Eosinophil cationic protein in perilesional skin of Incontinentia pigmenti Bloch-Sulzberger. - Selvaag, E.; Roald, B.; Larsen, T.E.; Thune, P. (European Journal of Pediatric Dermatology, 2018)
lncontinentia pigmenti Bloch-Sulzberger is a rare X-linked disorder, characterized by typical cutaneous eruptions, initially by vesicular lesions which later change to papular and then macular pigmentary lesions. Eosinophils are commonly found in involved tissue, but little is known about their role in the pathogenesis of the disease. We demonstrated deposition of eosinophil cationic protein (ECP) in the vesicular stage of the disease, especially in the perilesional region of involved skin. ECP was not seen in papular lesions. These characteristic findings suggest that toxic proteins of eosinophils play a major role in the development of vesicular changes in the early stage of lncontinentia pigmenti Bloch-Sulzberger.